2021 Methods-of-Payment Survey report - Christopher Henry; Matthew Shimoda; Julia Zhu (Bank of Canada, 2022)
We present results from the 2021 Methods-of-Payment (MOP) Survey, including updated payment shares based on a three-day shopping diary. We highlight long-term trends observed across previous MOP surveys from 2009, 2013 and 2017. We also review patterns of the management and use of cash, the adoption and use of payment cards, and the use of alternative payment methods across different demographic groups. Using other survey and data sources, we provide additional context for these results with respect to the COVID-19 pandemic
Keywords: D83; E41; 330; Bank notes; Digital currencies and fintech; Financial services; Coronavirus disease (COVID-19)